Go with the flow: the movement behaviour of fish from isolated waterhole refugia during connecting flow events in an intermittent dryland river. (21st January 2016) - Marshall, Jonathan C.; Menke, Norbert; Crook, David A.; Lobegeiger, Jaye S.; Balcombe, Stephen R.; Huey, Joel A.; Fawcett, James H.; Bond, Nick R.; Starkey, Alisa H.; Sternberg, David; Linke, Simon; Arthington, Angela H.
Summary: In many intermittent, dryland rivers, fish are confined to isolated waterholes for much of the year. It is only during brief flow events, which typify the hydrology of these systems, that fish are able to move between waterholes and explore surrounding habitat. Because most of the river channel will dry afterwards, there is a strong advantage for selection of persistent waterholes. Two hundred and fifteen individual fish of three common large‐bodied species were tagged in two isolated waterholes in the Moonie River (Queensland, Australia) over 3 years. Their movements were monitored to identify the flow events that trigger fish movement between waterholes, differences in response among species and size classes and refuge selection preferences. Some individuals of all species moved during flow events and others remained within the same waterhole. There was no clear upstream or downstream preference, and most individuals used a reach of up to 20 km, although some individuals ranged over more than 70 km in only several days. Above a threshold flow of 2 m above commence‐to‐flow level, timing of flow was more important than magnitude, with most movement occurring in response to the first post‐winter flow event, independent of its magnitude and duration. Many of the fish that moved displayed philopatry and subsequently returned to their starting waterhole either by the end of a flow event or on subsequent events, suggesting ability to navigate and a preference for more permanent refuge pools. Maximising survival in a highly variable environment provides a plausible mechanism for maintaining these behaviours. Modifications to both flow regime and hydrological connectivity may reduce movement opportunities for fish in intermittent rivers. Our findings show that fish in intermittent systems use networks of waterholes and that management and conservation strategies should aim to maintain movement opportunities at large spatial scales to preserve population resilience.